2005
DOI: 10.1016/j.jcf.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

MBL2 polymorphisms screening in a regional Italian CF Center

Abstract: We performed MBL2 genotyping in 47 CF patients-cared of at the regional CF Centre of Trieste-trying to establish a correlation within allelic variants of MBL2 and modification of patients' clinical outcome. FEV1 values were significantly lowered and a significantly earlier age at onset of Pseudomonas aeruginosa colonisation was found in CF patients with at least one MBL2 variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 11 publications
3
20
0
1
Order By: Relevance
“…The time-to-event analysis showed that MBL2 deficiency was strongly associated with earlier acquisition of P. aeruginosa in young children with CF (P = 0.0003; Figure 2). This modulatory effect most likely reflects the critical role of MBL2 in the first defense against bacterial colonization (16) and supports the similar but less significant effect previously observed in a small Italian CF patient cohort (42). However, it should be also noted that although MBL2 deficiency has been implicated in many studies as contributing to higher susceptibility to infections, there are also data suggesting the opposite (43).…”
Section: Discussionsupporting
confidence: 81%
“…The time-to-event analysis showed that MBL2 deficiency was strongly associated with earlier acquisition of P. aeruginosa in young children with CF (P = 0.0003; Figure 2). This modulatory effect most likely reflects the critical role of MBL2 in the first defense against bacterial colonization (16) and supports the similar but less significant effect previously observed in a small Italian CF patient cohort (42). However, it should be also noted that although MBL2 deficiency has been implicated in many studies as contributing to higher susceptibility to infections, there are also data suggesting the opposite (43).…”
Section: Discussionsupporting
confidence: 81%
“…Chronic Pa colonization is age-dependent and the majority of cystic fibrosis patients become colonized over time. Age at onset of Pa colonization is a more useful outcome parameter as earlier age correlates with poor prognosis [6,30,4,7,8,31].…”
Section: Discussionmentioning
confidence: 99%
“…a.) (Table 2) (Trevisiol et al 2005;Dorfman et al 2008;McDougal et al 2010). Because severity of lung disease, Ps.…”
Section: Lung Diseasementioning
confidence: 99%
“…MBL2 is biologically plausible, because of its role in innate immunity and the predilection of MBL2 deficient patients to bacterial and viral infection. Six studies involving .2000 CF patients have shown that MBL-deficient genotypes (OO or AO) are associated with worse lung function (Table 2) (Gabolde et al 1999;Garred et al 1999;Davies et al 2004;Yarden et al 2004;Trevisiol et al 2005;Dorfman et al 2008), and three studies reported earlier age of infection with Pseudomonas aeruginosa (Ps. a.)…”
Section: Lung Diseasementioning
confidence: 99%